Determinants of Internal Migration in Pakistan: Evidence from the Labour Force Survey, 1996-97 (The Pakistan Development Review, 2000)
The process of migration has diverse economic, social and environmental implications for the places of origin and destination. In the context of balanced regional growth and sustainable regional development it is important to study how internal migration affects the patterns of population distribution within a country. The spatial distribution of population is influenced by the characteristics of the sending and receiving areas in terms of push and pull factors resulting in rural-urban, urban-urban, rural-rural and urban-rural migration flows. As economies transform from being predominantly rural to being predominantly urban societies, the process of urbanisation assumes a rapid pace. Individuals migrate from rural to urban areas as a rational human capital investment decision to reap economic rewards in the form of better economic opportunities and benefits. The consequences of rapid urbanisation are multi faceted and require timely responses by development planners and policy-makers to deal with pressures created on the infrastructure of large urban centres by the influx of migrants. However, in some developing as well as developed countries, lately, there have been signs of a change in the trend of the population distribution away from concentration in a few large cities towards a more widespread distribution in medium-sized urban centres. The other dimension of this rural-urban migrant outflow manifests itself in the changing labour market scenario in the rural economy which loses the more productive members of its labour force to the urban economy.